Prevalence and Risk Factors of Diabetic Retinopathy in Diabetic Patients, Kalasin Province - ศรีจารนัย , สมยศ (Journal of Health Science of Thailand, 2011)
The objective of this survey research was to study prevalence and risk factors that related to diabetic retinopathy (DR) in diabetic patients, Kalasin Province. This research included in 4,060 diabetic patients in 5 districts, undergoing examination for DR during July - October 2008. The data was used to calculate frequency, percentage, means, standard deviation, chi-square and odds ratio. The results showed that diabetic patients were mostly women. 45 years old or more and on average, 57.9 years old; 79.21 percent were married; 92.02 percent completed primary school; 84.63 percent were in agriculture. It was found that 96.31 percent were type 2 diabetes mellitus; 56.70 percent had diabetes ≥ 5 years; 85.25 percent were treated by oral insulin; 47.34 percent had fasting plasma glucose ≤ 140 mg/dl; 27.29 percent were hypertension; 10.98 percent had hypercholesterol. The prevalence of DR was 12.19 percent. Most of the patients with DR had mild NPDR, 8.74 percent in right eye and 8.57 percent in left eye. PDR was found in 0.44 percent in right eyes and 0.37 percent in left eyes. Risk factors significantly correlated to DR were duration of diabetes, method of treatment, blood sugar control and hypertension (p<0.05). The patients with diabetes ≥ 5 years had 3.11 times more risk to DR than those with diabetes < 5 years. The patients, treated by drug had 4.27 times (95%CI 1.57,11.65) more risk to DR than the patients not treated by drug. The patients that had FBS ≥ 180 mg/dl had 2.07 times (95%CI 1.69,2.53) more risk to DR than FBS < 180 mg/dl. The patients with hypertension had 1.44 times (95%CI 1.17,1.76) more risk to DR than the patients with normal blood pressure.